ERANET JTC 2011: Submission and Activation of an International Academic Translational Project in Advanced Breast Cancer. Experience From the ET-FES Study - Monti, Manuela; Degenhardt, Tom; Brain, Etienne; Wuerstlein, Rachel; Argusti, Alessandra; Puntoni, Matteo; Rollandi, Gian Andrea; Corradengo, Davide; Boni, Luca; Ilhan, Harun; Nanni, Oriana; Cortes, Javier; et al. (Frontiers in Medicine, 2022)
Background: Academic research is important to face unmet medical needs. The Oncological community encounters many hurdles in setting up multicenter investigator-driven trials mainly due to administrative complexity. The purpose of a network organization at a multinational level is to facilitate clinical trials through standardization, coordination, and education for drug development and regulatory approval. Methods: The application of an European grant foresees the creation of a consortium which aims at facilitating multi-center academic clinical trials. Results: The ERA-NET TRANSCAN Call 2011 on "Validation of biomarkers for personalized cancer medicine" was released on December 2011. This project included Italian, Spanish, French and German centers. The approval process included Consortium constitution, project submission, Clinical Trial Submission and activation on a national level. The different timescales for submitting study documents in each Country and the misalignment of objections by each Competent Authority CA, generated several requests for changes to the study documents which meant amendments had to be made; as requested by the 2001/20/EC Directive, the alignment of core documents is mandatory. This procedure impacted significantly on study activation timelines. Time to first patient in was 14, 10, 28 and 31 months from the date of submission in Italy, France, Spain and Germany, respectively. Accrual was stopped on 22nd January 2021 due to an 18F FES shortage as the primary reason but also for having exceeded the project deadlines with consequent exhaustion of the funds allocated for the project. Conclusions: Pharmaceutical companies might be reluctant to fund research projects aimed at treatment individualization if the approval for a wider indication has already been achieved. Academic trials therefore become fundamental for promoting trials which are not attractive to big pharma. It was very difficult and time consuming to activate an academic clinical trial, for this reason, a study may become “old” as new drugs entered into the market. National institutions should promote the development of clinical research infrastructures and network with competence in regulatory, ethical and legal skills to speed up academic research.